1987
DOI: 10.1017/s1742758400022906
|View full text |Cite
|
Sign up to set email alerts
|

Host plant resistance to insects attacking soybean and mungbean in the tropics

Abstract: In the tropics, insect pests cause considerable damage to soybean, Glycine max and mungbean, Vigna radiata from germination until harvest and even in storage. Agromyzid flies in the seedling stage, lepidopterous and coleopterous defoliators in the vegetative and early reproductive stages, pentatomid and coreid bugs and lepidopterous pod-borers in the reproductive stage, and bruchids in storage all cause significant damage. Sources of resistance to agromyzids in mungbean (AVRDC accession V 4281), defoliators (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The use of ashes is an aordable pest management strategy, especially at subsistence level where only a small quantity of cowpea grains needs to be protected. In addition, ashes are non toxic, easily biodegradable, non pollutive and are known to be economically and environmentally acceptable to a majority of resource poor farmers in developing countries (Talekar 1987;Stoll 1988).…”
Section: Discussionmentioning
confidence: 99%
“…The use of ashes is an aordable pest management strategy, especially at subsistence level where only a small quantity of cowpea grains needs to be protected. In addition, ashes are non toxic, easily biodegradable, non pollutive and are known to be economically and environmentally acceptable to a majority of resource poor farmers in developing countries (Talekar 1987;Stoll 1988).…”
Section: Discussionmentioning
confidence: 99%
“…The most severe outbreaks tend to be in the northeastern Heilongjiang, Jilin, and Liaoning Provinces, which coincides with areas where approximately two-thirds of soybeans are grown in China [53], making L. glycinivorella a primary pest of this crop. Although foliar insecticides are applied, effective contact and reduction in feeding damage is difficult to achieve due to protection of larva under G. max leaf canopies and within pods [54]. Use of systemic insecticides can lead to more consistent reductions in L. glycinivorella feeding damage, but ecological concerns limit their use especially given evidence of impacts on pollinator health [55].…”
Section: Introductionmentioning
confidence: 99%
“…have been reported on soybeans (Ezueh & Dina, 1979;Jackai et al 1985). Defoliators reduce yields and the extent of losses depends on the level of defoliation and the growth stage of the soybean plant (Talekar, 1987). Thomas et al (1974) and Thomas (1985) reported that removal of one-third of the leaves at seed development stage caused 13.8% (= 395 kg/ha) and 22.8% (= 661 kg/ha) yield reductions, respectively.…”
Section: Introductionmentioning
confidence: 99%